2020
DOI: 10.1017/s136898001900524x
|View full text |Cite
|
Sign up to set email alerts
|

Cassava consumption and the occurrence of cyanide in cassava in Vietnam, Indonesia and Philippines

Abstract: Objective: To make a tentative assessment of the consumption of cassava in three countries in South-east Asia and the cyanogenic potential (CNp) of the crop as a possible food safety issue. Design: We used data from the Ministry of Health in Vietnam and Statistics Authorities in Indonesia and Philippines (mean household consumption per province) to assess cassava consumption. Conversions of units were needed to facilitate the comparison of cassava consumption between countries. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Cassava with low HCN content (less than 100 ppm in fresh roots) is known as sweet cassava and can be consumed cooked or processed [22]. However, there is another report that cassava with HCN content < 50 ppm in fresh roots is called sweet cassava, while cassava with HCN concentration ≥50 ppm in fresh root is called as bitter cassava [23]. I is also reported that the maximum cyanogenetic potential for human consumption is 50 ppm for fresh root [24].…”
Section: Quality Attributesmentioning
confidence: 99%
“…Cassava with low HCN content (less than 100 ppm in fresh roots) is known as sweet cassava and can be consumed cooked or processed [22]. However, there is another report that cassava with HCN content < 50 ppm in fresh roots is called sweet cassava, while cassava with HCN concentration ≥50 ppm in fresh root is called as bitter cassava [23]. I is also reported that the maximum cyanogenetic potential for human consumption is 50 ppm for fresh root [24].…”
Section: Quality Attributesmentioning
confidence: 99%